Facile synthesis of hierarchical porous manganese nickel cobalt sulfide nanotube arrays with enhanced electrochemical performance for ultrahigh energy density fiber-shaped asymmetric supercapacitors. Issue 17 (19th April 2018) - Wang, Xiaona; Zhang, Qichong; Sun, Juan; Zhou, Zhenyu; Li, Qiulong; He, Bing; Zhao, Jingxin; Lu, Weibang; Wong, Ching-ping; Yao, Yagang
Abstract : Hierarchical porous manganese–nickel–cobalt sulfide multi-tripod nanotube arrays on carbon nanotube fibers are prepared by a simple, cost-effective synthesis process. Abstract : To create high energy density fiber-shaped supercapacitors (FSCs), a new class of hierarchical electrodes with high electrical conductivity and good mechanical stability is needed. Here, a novel electrode consisting of porous manganese–nickel–cobalt sulfide (MNCS) multi-tripod nanotube arrays (NTAs) on carbon nanotube fibers (CNTFs) is prepared by a facile and cost-effective synthesis. The MNCS NTAs/CNTF electrode achieves a high specific capacitance of 2554.5 F cm −3, which is attributed to the high electrical conductivity and richer redox reactions of MNCS NTAs resulting from mixing three metal elements followed by sulfidation, and high porosity but a robust architecture. The unique features of these electrodes allowed us to successfully fabricate a fiber-shaped asymmetric supercapacitor (FASC) with a maximum operating voltage of 1.6 V by using the vanadium nitride (VN) nanowires (NWs) on CNTF electrode as the negative electrode. A volumetric capacitance of 147.3 F cm −3 and an energy density of 52.4 mW h cm −3 of the as-obtained FASC device are higher than those reported for similar devices. In addition, our FASC device possesses outstanding reliability and achieves a retaining capacitance of 92.9% after 5000 bending cycles. Thus, this work develops hierarchical, porous MNCS multi-tripod NTAs as a promising candidate for next-generation electrode materials with high electrochemical performance.